Perusahaan Otomobil Nasional Berhad: Maintaining Dominance In The Malaysian Automobile Industry - Camillus, Nillian (2005)
In order to remain competitive as well as to contribute to national economy, PROTON needs to improve on productivity, explore opportunity to diversify in the income base, wider the model of car , comprehensive coverage on corporate governance policies and mechanism, explore new marketing approaches and intensify technology.